Model of Character Education for Early Childhood Eduwisata Ndalem Kerto through Outing Class Activities - Rido Kurnianto; Aldo Redho Syam; Katni Katni; Risyan Nurhakim (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
This study examines the character education model by Eduwisata Ndalem Kerto Ponorogo through outing class activities. It examines the level of success in instilling various characters developed in Indonesia for early childhood. The research approach uses descriptive qualitative field research type. Data collection techniques are carried out by observation related to the early childhood character education model, interviews with managers, teachers and students during outing classes and documentation of outing class activities. Data analysis is done by organizing, interpreting, presenting data narratively, and drawing conclusions. The study results revealed that the early childhood character education model through outing classes at Eduwisata Dalem Kerto includes gardening activities, learning fun, interaction with livestock, and cooking fun. This outing class activity is designed for 2 hours and is guided directly by the instructor from beginning to end. The results of the character education model through outing classes effectively instil various early childhood characters from characters developed in Indonesia. It should be noted that this study is still limited to the early childhood character education model using outing classes in eduwisata. The findings of this study provide originality in the form of a character education model for early childhood through outing classes in the form of gardening, learning fun, cooking fun and livestock edu-tourism that can be used as a fun and meaningful early childhood education model. These findings provide many contributions to the enrichment of character education models, specifically character education for early childhood which is rich in stimulation that develops the character and intelligence of early childhood.